Nutrition-related policies and programs: past performance and research needs. - Kennedy, Eileen T.; Pinstrup-Andersen, Per; Adams, Richard H., Jr. (International Food Policy Research Institute, 1983)
There is an urgent need for research that will assist the governments of developing countries, international institutions, external assistance agencies, and other institutions in choosing, designing, modifying, and implementing effective and efficient nutrition-related programs and policies. On the basis of an extensive review of the literature and interaction with a large number of informed persons, we have identified the knowledge gaps and research needs believed to be most critical and have outlined research that should be given high priority and that should bring high returns.